Factors affecting connectivity and sediment yields following wildfire and post‐fire salvage logging in California's Sierra Nevada. Issue 1 (3rd December 2020) - Olsen, Will H.; Wagenbrenner, Joseph W.; Robichaud, Peter R.
Abstract: Sediment delivery following post‐fire logging is a concern relative to water quality. While studies have assessed the effect of post‐fire logging on sediment yields at different spatial scales, none have explicitly identified sediment sources. Our goal was to quantify post‐fire and post‐salvage logging sediment yields and use rill patterns to identify sediment sources. We measured the extent and type of logging disturbance, length of rills per unit area or "rill density", ground cover, and sediment yields in nine logged and five control small catchments or "swales", 0.09 to 0.81 ha, for 5 years after the 2013 Rim Fire in California's Sierra Nevada. The logged swales had a mean ground disturbance of 31%. After the first wet season following logging, there was no difference in either mean rill density (0.071 and 0.088 m m −2, respectively) or mean transformed, normalized sediment yields between the control and logged swales. Untransformed mean sediment yields across three sites ranged from 0.11–11.8 and 1.1–3.2 Mg ha −1 for the controls and salvage‐logged swales, respectively. Rill density was strongly related to sediment yield and increased significantly with the amount of high‐traffic skid trail disturbance in logged swales. Rill density was not significantly related to the amount of bare soil despite a significant relationship between sediment yields and bare soil. Rills usually initiated in bare soil and frequently connected high traffic skid trails to the drainage network after being diverted by waterbars. Rill connectivity and sediment yields decreased in control and logged swales where vegetation or other surface cover was high, suggesting this cover disconnected rills from the drainage network. Increasing ground cover on skid trails and between areas disturbed by post‐fire logging and stream channels may reduce sediment yields as well as the hydrologic connectivity between hillslopes and the drainage network. Abstract : Following the 2013 Rim Fire and subsequent salvage logging, no significant difference in sediment yield or rill density was found between logged and unlogged small catchments. Rill density was highly correlated to initial sediment yields, and yields were also positively correlated with exposed bare soil extent. Rill density within logged catchments increased with skid trail extent, and exposed bare soil patches were frequently connected by rills to the drainage network.